Low-protein diet supplemented with ketoacids delays the progression of diabetic nephropathy by inhibiting oxidative stress in the KKAy mice model. Issue 1 (6th December 2017) - Liu, Dongmei; Wu, Ming; Li, Lin; Gao, Xiang; Yang, Bo; Mei, Shuqin; Fu, Lili; Mei, Changlin
Abstract: Diabetic nephropathy (DN) is a major cause of chronic kidney disease. We aimed to investigate the effect of the low-protein diets (LPD) supplemented with ketoacids (LPD+KA) in KKAy mice, an early type 2 DN model. KKAy mice were treated with normal protein diet (NPD), LPD or LPD+KA from 12 to 24 weeks of age. A period of 12-week treatment with LPD significantly reduced albuminuria as compared with that observed after NPD treatment. Treatment with LPD+KA further reduced albuminuria as compared with that observed with LPD treatment alone. Moreover, LPD treatment reduced mesangial expansion, thickness of glomerular basement membrane and the severity of the podocyte foot process effacement in KKAy mice; these effects were more pronounced in KKAy mice treated with LPD+KA. Both LPD and LPD+KA treatments slightly reduced total body weight, but had no significant effect on kidney weight and blood glucose concentrations when compared with NPD-treated KKAy mice. LPD treatment slightly attenuated oxidative stress in kidneys as compared with that observed in NPD-treated KKAy mice; however, LPD+KA treatment remarkably ameliorated oxidative stress in diabetic kidneys as shown by decreased malondialdehyde concentrations, protein carbonylation, nitrotyrosine expression and increased superoxide dismutase expression. Nutritional therapy using LPD+KA confers additional renal benefits as compared with those of LPD treatment alone in early type 2 DN through inhibition of oxidative stress.